Determinants of Financial Statement Fraud in Perspective Hexagon Fraud Theory - Dini Febriani; Ari Dewi Cahyati; Anisa Putri; Neneng Lasmita Susanti (Basic and Applied Accounting Research Journal, 2022)
The purpose of this research is to analyze the effect of the hexagon fraud theory; stimulus, opportunity, rationalization, capability, ego, collusion, company size on financial statement fraud in energy sector companies listed on the Indonesia Stock Exchange in 2016-2020 using the F-Score model as a measurement. This study uses a sample of 39 energy sector companies with a total of 186 observations. This study uses multiple regression analysis techniques. The results of this study indicate that the stimulus (pressure) in terms of financial targets and external pressure and opportunity in terms of the nature of industry affects financial statement fraud. While rationalization in terms of change in auditors, capability in terms of change in directors, ego (arrogance) in terms of CEO duality, collusion in terms of market performance ratios, and company size have no effect on financial statement fraud.